2017
DOI: 10.1002/btpr.2530
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a cathepsin D protease from CHO cell‐free medium and mitigation of its impact on the stability of a recombinant therapeutic protein

Abstract: During purification process development of a recombinant therapeutic protein, an endoproteolytic activity endogenous to the Chinese hamster ovary (CHO) cells and leading to degradation at particular hydrophobic amino acid residues (e.g., Phe and Trp) was observed when processing at acidic pH. The presence of residual levels of protease activity in purified protein batches affected the inherent activity of the product when stored as a solution. To develop a robust purification strategy to minimize this undesira… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 13 publications
0
25
0
Order By: Relevance
“…A more likely cause for the increase in aggregates and fragments could be the presence of proteases—it has previously been reported that proteases are produced during late stage cell culture and can cause product fragmentation. Cathepsin D in particular is known to co‐purify and cleave the antibody product . Accumulation of fragments could also lead to the formation of aggregates.…”
Section: Resultsmentioning
confidence: 99%
“…A more likely cause for the increase in aggregates and fragments could be the presence of proteases—it has previously been reported that proteases are produced during late stage cell culture and can cause product fragmentation. Cathepsin D in particular is known to co‐purify and cleave the antibody product . Accumulation of fragments could also lead to the formation of aggregates.…”
Section: Resultsmentioning
confidence: 99%
“…CHO cells are widely used for production of recombinant glycoprotein therapeutics due to their high productivity (1-10 g per liter), genetic stability and ability to grow in large-scale suspension culture [199][200][201] in serum-free medium. However, many recombinant proteins, including monoclonal antibodies, antibody fusion proteins and IFN-γ, are partially degraded or proteolyzed by endogenous CHO cell proteases during the cell culture or recovery process [202][203][204][205][206][207]. Novel approaches to solve proteolysis and enhance glycosylation for production of HIV envelope proteins as vaccine candidates are being explored [208].…”
Section: Mammalian Cellsmentioning
confidence: 99%
“…PLBL2 was identified to interact with different mAbs and to "hitchhike" through the entire process, resulting in degradation of some of the formulation components. Cathepsin D was found to cause mAb degradation in the formulated drug product (Bee et al, 2015) and various strategies have been used to remove residual cathepsin D, either by optimal washes during protein A capture or by thermal inactivation of the protease (Lim et al, 2017). Cathepsin D was found to cause mAb degradation in the formulated drug product (Bee et al, 2015) and various strategies have been used to remove residual cathepsin D, either by optimal washes during protein A capture or by thermal inactivation of the protease (Lim et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Although high clearance of HCPs are often achieved as determined by enzyme-linked immunosorbent assay (ELISA; X. Wang, Hunter, & Mozier, 2009), there may still be specific HCPs in the final product that can cause degradation of the drug product or elicit an immune response in patients (Bee et al, 2015;Fischer et al, 2017;Gao et al, 2011;Lim et al, 2017;Robert et al, 2009). Thus, it is important to identify and characterize these HCPs and to design efficient separation processes for their removal.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation